'Students don't always tell teachers the truth very often, do they?' Reflections on the implications when teachers and students collaborate to investigate teaching practice (UCL Press, 2016)
Informed by Martin Buber's notions of I-It and I-Thou relationships, this paper examines the problematic and contested issues of emancipation and empowerment in schooling. Specifically, it explores what happens when teachers and students collaborate when observing lessons and commenting on teaching practice in the imagined space of the self-improving school system. Within this space, it examines the challenges and complexities of establishing I-Thou teacher-student relationships, and the potential for creative dissonance in such situations. Finally, it explores the idea that the self-improving school could become a place where teachers and students create a space for mutual dialogue about collaborative research in the classroom - in other words, a place where classroom practice is democratically 'top-down' teacher-led and 'bottom-up' student-informed.